Inferior vena cava filters (IVCFs): a review of uses and application to international guidelines at a single Australian center; implications of venous thromboembolism associated with malignancy. (1st May 2018) - Craven, Philip; Daly, Ciara; Oates, Randall; Sikotra, Nisha; Clay, Tim; Gabbay, Eli
Abstract : Venous thromboembolism (VTE) is a potentially lethal event. Anticoagulation is the cornerstone of treatment. Inferior vena cava filters (IVCFs) may be used in circumstances when anticoagulation is contraindicated or as an adjunct to anticoagulation. IVCF use is not without controversy due to concerns over their safety profile, differences in guidelines from international societies, and a limited randomized control trial evidence. We retrospectively undertook a review of IVCF use over a three‐year period (2014–2016) at our center, which has a large oncology service but no trauma unit. There were 44 patients with successful IVCF insertion and one patient with an unsuccessful attempt. Indications for insertion included: a contraindication to anticoagulation (n = 28); recurrent VTE on anticoagulation (n = 10); and extensive VTE (n = 7). There were 13 retrieval attempts, of which ten were successful. There were five documented IVCF complications (tilting: n = 2, IVC thrombus: n = 3) with one episode of IVCF failure and two episodes of deep vein thrombosis during the follow‐up period. Of the patients, 71% had an active malignancy (of whom 71% had metastatic disease). Seventeen patients died due to progressive malignancy during the study period. There were no life‐threatening VTEs or IVCF‐associated mortalities. Adherence with published international guidelines was variable. Patients with malignancy were less likely to undergo IVCF retrieval and had a reduced rate of retrieval success. None of the international guidelines comment on the use of IVCFs in patients with malignancy despite being commonly used. IVCF use may be an underappreciated tool in this group.